Determinan Overpricing Saham pada Saat Initial Public Offering di Bursa Efek Indonesia - Ulfah, Atika; Qodri, Lailatul; Febriani, Erni (Penerbit Goodwood, 2023)
Purpose: This study aimed to prove the effect of financial leverage, company size, company age and underwriter’s reputation on stock overpricing. Method: The population of this research was the companies which conducted initial public offering (IPO) which were listed on the Indonesia Stock Exchange in 2011 - 2020. This research used purposive sampling technique and the number of samples obtained was 62 companies. Results: The results of this study indicate that the variable company size, company age, and underwriter reputation have a positve effect on overpricing, financial leverage have a negative effect on overpricing. Limitations: This study does not test the type of industry and the level of industrial saturation of companies conducting an IPO. This study does not look at the agreement between the issuer and the underwriter whether it is full commitment or not. Contribution: This research is expected to increase knowledge about the factor that influence overpricing of share during the initial public offering on the Indnesia Stock Exchange.